Avocado (Persea americana Mill.) postharvest status, breakthrough and processing - Forero, Freddy; García, Jairo; Cárdenas-Hernández, Julián F. (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2011)
Avocado is a very wanted fruit worldwide for its consistency, exquisite taste, high nutritional value and its wide potential use not just for cooking, but also in cosmetic and pharmaceutical processes. Despite this, the technological advances developed in the productive chain of avocado, are nor spread and transferred in an effective way to producers and dealers. In the current article are collected and analyzed studies that have been reported in specialized literature, in the postharvest area. Topics as refrigerated storage, ethylene regulation, modified atmospheres and microorganisms control, were discussed being the most applied techniques to maintain the fresh quality of this fruit. In the avocado processing are shown some developed technological alternatives used for the conservation and utilization of pulp, oil and seed, also a description of the uses and perspectives that have these raw materials in the development of non traditional products.